Pola Peresepan Obat pada Pasien Diare Anak di Instalasi Rawat Inap RSUD dr. Abdoer Rahem-Situbondo - Ninda Titis Ainorrochma; Ema Rachmawati; Diana Holidah (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Diarrhea is defined clinically as increased bowel movements more than three times a day, accompanied by changes in stool consistency (becoming liquid) with or without blood within 24 hours. This disease often occurs in patients aged under five to children - children, usually lasts for several days, so that the body can lose important fluids such as water and salt needed for survival. Most patients die from diarrhea due to severe dehydration and fluid loss. This research was conducted to determine the pattern of drug prescription in pediatric diarrhea patients which includes the types and classes of drugs and how to administer the drug. The research method used was purposive sampling and using a retrospective descriptive approach. The sample of this study was diarrhea patients for children aged 0 months to 1 year who received treatment at the inpatient installation at RSUD dr. Abdoer Rahem Situbondo from January to December 2019. The treatment of diarrhea treatment included rehydration, antidiarrheal, antimicrobial, analgesic-antipyretic and other drug classes such as antacids, anticonvulsants and mucolytics. From 108 samples of pediatric diarrhea patients found 82 patients (75.96%) used antimicrobial drugs.